Usefulness of Lung Ultrasound in the Diagnosis of Community-acquired Pneumonia in Children - Meng-Chieh Ho; Chin-Ru Ker; Jong-Hau Hsu; Jiunn-Ren Wu; Zen-Kong Dai; I-Chen Chen (Elsevier, 2015)
Pneumonia is a life-threatening disease in children. With the current lack of universal diagnostic criteria, the diagnosis is usually made on clinical manifestations and findings from chest radiographs. Ultrasonography has recently been applied to the detection of pulmonary diseases. However, few data have been published showing its effectiveness in detecting pneumonia in children. The objective of this study was to determine the power of lung ultrasonography (LUS) for the diagnosis of pneumonia in children. Methods: This retrospective study was carried out by reviewing medical records. Patients admitted to a pediatric ward with a diagnosis of pneumonia from June 1, 2010 to December 31, 2012 were enrolled in this study. Personal information, laboratory data, characteristics on LUS scan, and the results of chest radiography and LUS were collected. We compared the detection rate of pneumonia by chest radiography and LUS. LUS scans were followed up in 23 patients during the progression of their disease. Results: A total of 163 patients was enrolled. Chest radiography was able to detect pneumonia in 152 patients, whereas LUS detected pneumonia in 159 patients. In LUS, the positive rates of the comet-tail sign, air bronchograms, fluid bronchograms, vascular pattern within the consolidation, and pleural effusion were 50.9%, 93.7%, 20.1%, and 28.9%, respectively. During follow up, the average size of the pneumonia patch in 23 patients decreased from 10.9 ± 8.7 cm2 to 5.5 ± 8.2 cm2, and finally to 2 ± 1.9 cm2 on Day 1, Days 3-5 and Days 7-14, respectively. Conclusion: LUS is a sensitive diagnostic tool with which to identify pneumonia in children. It is also useful in following up the progress of pneumonia. We suggest that LUS is a complementary tool to chest radiography in the diagnosis of pneumonia in children and that the follow up of pneumonia by LUS can reduce the exposure of children to ionizing radiation.